BƯỚC ĐẦU ĐÁNH GIÁ KẾT QUẢ ĐIỀU TRỊ UNG THƯ THỰC QUẢN GIAI ĐOẠN TÁI PHÁT/ DI CĂN BẰNG LIỆU PHÁP MIỄN DỊCH PEMBROLIZUMAB TẠI BỆNH VIỆN UNG BƯỚU NGHỆ AN (Vietnam Journal of Community Medicine, 2026)
Aims: To evaluate the result of Pembrolizumab-containing regimens in patients with recurrent or metastatic Esophageal Cancer at Nghe An Oncology HospitalMethod: A retrospective descriptive study was conducted on 19 patients with recurrent or metastatic Esophageal Cancer who received Pembrolizumab-containing regimens in Nghe An Oncology Hospital from March 2023 to May 2026Results: The average age of 19 patients was 61,4. At the time of treatment, distant metastases were identified in 36,8% of patients. Pembrolizumab was administered as a first-line treatment in 73,7% of cases. After 6 cycles of Pembrolizumab, the disease control rate (DCR) was 71.4%, the overal response rate (ORR) was 42,8% and  the  median  PFS  was  9,2 months; The most common was neutropenia (63,2%), anemia (57,9%), most of them were grade 1, 2.Conclusion Pembrolizumab-containing regimens demonstrated clinical efficacy and acceptable toxicity in patients with recurrent or metastatic esophageal cancer.
Keywords: Esophageal cancer, recurrent/metastatic, Pembrolizumab